A uhf planar monopole antenna for cognitive radio application - Jusoh, Muzammil (2010)
This project report presents the design, simulation and measurement of a UHF Planar Monopole Antenna for Cognitive Radio Application. This project covered for broadcasting frequency that has been allocated by MCMC (Malaysian Communication & Multimedia Commission) from 470MHz to 960MHz. The objective is to reduce the antenna dimensions for the UHF frequency. The methods introduced are the beveling technique and the lump element. Some simulation studies have carried out of the effect of chip resistor, chip capacitor and chip inductor to two different single antennas. All the simulation results are obtained by using CST Studio Suite software in terms S-Parameter analysis, VSWR (voltage standing wave ratio), the radiation pattern and the gain of the antenna. While the antennas are fabricated on the Flam Resistance Board (FR4 Board) due to the low cost and it can cover for the required frequency. There are two antennas produced by the end of this project, which the first antenna embedded with the resistor and the second antenna is without the resistor. Measurement process is done by the ZVL Rohde & Schwarz network analyzer. The presented performances clarify the potential of the approach between simulation result and the hardware result.